Ultrafiltration of Natural Organic Matter (NOM): Effect of NOM Characteristics on Membrane Rejection Mechanisms in Drinking Water Process - A.W, Zularisam; A.F, Ismail; M.R, Salim (Malaysian Journal of Science, 2007)
The main objective of this research is to study on the influence of NOM characteristics on the membrane rejection mechanisms. Polysulfone (PSF) and cellulose acetate (CA) membranes formed by a simple phase inversion technique were used in this study. The experiments were carried out through a hydrophobic 68 kDa MWCO PSF and a hydrophilic 50 kDa MWCO CA of a submerged ultrafiltration (UF) membrane reactor. The Ulu Pontian Kecil river water was fractionated into several components which were hydrophobic (HPO), transphilic (TPI) and hydrophilic (HPI) fractions using DAX-8 and XAD-4 ion exchange resins. The isolated surface water components were characterized by dissolved organic carbon (DOC), ultra violet absorbance at 254 nm (UV$_{254nm}$), specific ultraviolet absorbance (SUVA) or a measure of relative abundance of relative aromaticity, etc. The experimental results showed that the hydrophilic component of NOM exhibited the worst flux decline despite lesser DOC and UV rejection compared to other fractions (HPO and TPI). The electrostatic interaction has been found to play a more influential role than steric hindrance mechanism when filtering NOM fractions with a negatively charged membrane. The quantitative results of Resistance in-Series Model analysis on clean and fouled membranes elucidated that both reversible and irreversible fouling mechanisms occurred during surface water filtration.